College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Section P.7 - Rational Expressions - P.7 Exercises - Page 51: 70



Work Step by Step

We multiply through by $xy(x+y)$ to get rid of excess fractions. Then we simplify: $\displaystyle \frac{x^{-1}+y^{-1}}{(x+y)^{-1}}=\frac{\frac{1}{x}+\frac{1}{y}}{\frac{1}{x+y}}=\frac{\frac{1}{x}+\frac{1}{y}}{\frac{1}{x+y}}*\displaystyle \frac{xy(x+y)}{xy(x+y)}=\frac{y(x+y)+x(x+y)}{xy}=\frac{xy+y^{2}+x^{2}+xy}{xy}=\frac{x^{2}+2xy+y^{2}}{xy}=\frac{(x+y)^{2}}{xy}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.